2001
DOI: 10.1103/physreve.64.056229
|View full text |Cite
|
Sign up to set email alerts
|

Breathing current domains in globally coupled electrochemical systems: A comparison with a semiconductor model

Abstract: Spatio-temporal bifurcations and complex dynamics in globally coupled intrinsically bistable electrochemical systems with an S-shaped current-voltage characteristic under galvanostatic control are studied theoretically on a one-dimensional domain. The results are compared with the dynamics and the bifurcation scenarios occurring in a closely related model which describes pattern formation in semiconductors. Under galvanostatic control both systems are unstable with respect to the formation of stationary large … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…The three qualitatively different spatio-temporal patterns (breathing, antiphase and hopping) observed on the top of the packed-bed reactor look strikingly similar to those experimentally observed in 2-D domains in electrochemical field (Hudson et al, 1993;Plenge et al, 2001;Birzu et al, 2003;Lee et al, 2003). Birzu et al (2003) concluded that the evolution of these spatio-temporal patterns during electrodissolution of a metal disk electrode was caused by the presence of (negative) global coupling.…”
Section: Discussionsupporting
confidence: 53%
“…The three qualitatively different spatio-temporal patterns (breathing, antiphase and hopping) observed on the top of the packed-bed reactor look strikingly similar to those experimentally observed in 2-D domains in electrochemical field (Hudson et al, 1993;Plenge et al, 2001;Birzu et al, 2003;Lee et al, 2003). Birzu et al (2003) concluded that the evolution of these spatio-temporal patterns during electrodissolution of a metal disk electrode was caused by the presence of (negative) global coupling.…”
Section: Discussionsupporting
confidence: 53%
“…Globally coupled oscillatory systems have been studied both experimentally and theoretically in a variety of systems including chemical reactions [10,11,12,13,14,15], metabolic oscillators [16,17], electrochemical oscillators [18,19,20,21,22,23,24,25,26,27,28], catalytic reactions [29], neuronal networks [5,30,31,32,33,34,35], salt-water oscillators [36], laser arrays [37], and cardiac oscillators [38,39]. Theoretical studies have been performed using activator-inhibitor type models that explicitely describe the dynamics of the participating physical (chemical, biological, etc) variables.…”
Section: Introductionmentioning
confidence: 99%
“…Global feedback (a closed-loop control, as opposed to open-loop control or external forcing) has been shown to generate a variety of patterns, including cluster states in oscillatory active media [10]. Experimental and theoretical studies in the CO oxidation on platinum surfaces [11][12][13][14][15][16] and other catalytic processes [17,18], as well as in electrochemistry [19] or in semiconductors [20,21], have shown that global feedback can be employed to control propagating waves and to generate spatially periodic patterns such as Turing patterns or traveling waves (for a review see [22]). …”
Section: Introductionmentioning
confidence: 99%